KORELASI PERSEPSI CITRA TUBUH TERHADAP STATUS GIZI ORANG DEWASA DI DESA PANCUR, MAYONG, JEPARA - Cyntia Ratna Sari; Hanifah Maharani (ARKA INSTITUTE, 2022)
Lockdown during the Covid-19 pandemic caused changes in the perception of hunger, satiety and increased eating behavior in people around the world. As many as 48% of people feel their weight has increased. The increase in the incidence of obesity is inevitable. Obesity is widely associated with poor body image. This study wanted to explore differences in BMI and body image perceptions between men and women and the correlation between body image perceptions and nutritional status. This research is an analytical observational using a cross sectional design. The study took a population of adults living in Pancur Village, Mayong, Jepara with purposive sampling technique. Correlation test using Spearman's rank and (r) to see the strength of the relationship between body image perception and BMI. While the independent t-test to see differences in perception and BMI in adult men and women. The results of the Independent t-test showed that there were differences in body image perceptions for men and women, there were differences in BMI for men and women (p<0.05), and the Spearman rank test had a positive correlation between body image perceptions and BMI Nutritional status. (p<0.0009). Adult men and women have different perceptions of body image and nutritional status. Adult women are more concerned about the perception of their body image for themselves and in the eyes of others than adult men. The better the perception of body image, the closer the nutritional status to normal.